Soil COS Exchange: A Comparison of Three European Ecosystems. Issue 4 (14th April 2020) - Kitz, Florian; Spielmann, Felix M.; Hammerle, Albin; Kolle, Olaf; Migliavacca, Mirco; Moreno, Gerardo; Ibrom, Andreas; Krasnov, Dmitrii; Noe, Steffen M.; Wohlfahrt, Georg
Abstract: The potential of carbonyl sulfide (COS) flux measurements as an additional constraint for estimating the gross primary production depends, among other preconditions, on our understanding of the soil COS exchange and its contribution to the overall net ecosystem COS flux. We conducted soil chamber measurements of COS, with transparent chambers, in three different ecosystems across Europe. The in situ measurements were followed by laboratory measurements of soil samples collected at the study sites. The soil samples were exposed to UV radiation to investigate the role of photo‐degradation for COS exchange. In situ and laboratory measurements revealed pronounced intersite and intrasite variability of COS exchange. In situ COS fluxes were primarily governed by radiation in the savannah‐like grassland (SAV), soil temperature and intrasite heterogeneity in the deciduous broadleaf forest, and soil water content and intrasite heterogeneity in the evergreen needleleaf forest. The soil of the ecosystem with the highest light intensity incident on the soil surface, SAV, was a net source for COS, while the soils of the other two ecosystems were COS sinks. UV radiation increased COS emissions and/or reduced COS uptake from all soil samples under laboratory conditions. The impact of UV on the COS flux differed between soil samples, with a tendency toward a stronger response of the COS flux to UV radiation exposure in samples with higher soil organic matter content. Our results emphasize the importance of photo‐degradation for the soil COS flux and stress the substantial spatial variability of soil COS exchange in ecosystems. Key Points: COS emissions increased after UV exposure of soil samples from three European soils Primary abiotic driver of COS cycling differs between three European soils